2004
DOI: 10.17221/465-pps
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and host plants on the development and fecundity of the spider mite Tetranychus urticae (Acarina: Tetranychidae)

Abstract: 142Vol. 40, Plant Protect. Sci. & H��� 1983; P������ et al. 1984) in fecundity of the spider mite at higher temperatures. 1983) or decrease (B���� MATERIAL AND METHODSTetranychus urticae was reared on plants of green bean in laboratory conditions at a temperature of 23°C (± 2°C). Development and fecundity of the mite was determined in an air-conditioned box at diverse temperatures (15, 20, 25, 30 and 35°C) and on three host plants (Cucumis sativus L., Capsicum annuum L. and Phaseolus vulgaris L.). The leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 10 publications
4
23
0
2
Order By: Relevance
“…Several studies have shown that the optimal temperature for T. urticae is around 35°C and that the lower and upper temperature thresholds are about 10°C and 38°C, respectively (Gutierrez 1976;Bounfour and Tanigoshi 2001;Praslicka and Huszar 2004). According to our study, the optimal temperature for development rate of S. longicornis was about 36°C for female and the upper one varied All nonlinear models fitted the data of this study very well as indicated by the high values of R 2 and R adj 2 .…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have shown that the optimal temperature for T. urticae is around 35°C and that the lower and upper temperature thresholds are about 10°C and 38°C, respectively (Gutierrez 1976;Bounfour and Tanigoshi 2001;Praslicka and Huszar 2004). According to our study, the optimal temperature for development rate of S. longicornis was about 36°C for female and the upper one varied All nonlinear models fitted the data of this study very well as indicated by the high values of R 2 and R adj 2 .…”
Section: Discussionsupporting
confidence: 78%
“…Developmental time was intermediate on JT×MYD hybrid and NL, being reduced by 9.6 and 13.4%, respectively in relation to JT. Furthermore, effect of coconut cultivar on R. indica Host plant effect on phytophagous mite species reproduction was previously shown as growing, without effect, or decreasing (Ribeiro et al, 1988;Hilker and Meiners, 2002;Praslička and Huszár, 2004). Differences in R. indica developmental time was observed when reared on coconut cultivars, being 21.5 and 19.8 d on JT (in Trinidad) and on a hybrid MYDxJT (in Venezuela), respectively (Vásquez et al, 2015).…”
Section: Biological Aspects Of R Indica Reared On Different Coconut mentioning
confidence: 88%
“…An effect of host plant on mite reproduction has been established for several Tetranychid species (e.g., de Ponti 1977; Ribeiro et al 1988;Hilker & Meiners 2002;Praslička & Huszár 2004). Previous studies have demonstrated that grape leaves and fruits synthesize phenolic compounds in response to fungal attacks or abiotic factors (Morrissey & Osbourn 1999).…”
Section: The Avocado Brown Mite Oligonychus Punicae Hirstmentioning
confidence: 99%